AN OVERVIEW OF ISLAMIC LAW AGAINST BUYING AND SELLING SAND-LAND WITH A LIBERATION SYSTEM - Mochammad Nuril Misbach; Muhammad Nafik Hadi Ryandono; Ari Prasetyo (Universitas Airlangga, 2019)
Buying and selling as a meant to get goods easily, one could exchange money with goods he needed the seller. Of course with the value agreed upon by both parties. The law of buying and selling were permissible basically, It was meaning that every Muslim in earning a living could by meant of buying and selling. The aim was to describing and analyzing the perspective of Islamic law about buying and selling Sand-Land with a systems slash of case studying Mount Wurung with the views of Islamic law. The research was used qualitative method with descriptive analysis. According to Madzhab of Imam Hanafi allowed the buying and selling which contained a little gharar because the buying and selling had been estimated based on experience that was close to truth and buying and selling including buying and selling named jizaf, whereas according to Madzhab of Imam Syafi'i was not permitted because there was potential gharar which allowed each of them had a loss or profit.